Recombinant influenza H7 hemagglutinins induce lower neutralizing antibody titers in mice than do seasonal hemagglutinins. Issue 6 (12th September 2014) - Blanchfield, Kristy; Kamal, Ram P.; Tzeng, Wen‐Pin; Music, Nedzad; Wilson, Jason R.; Stevens, James; Lipatov, Aleksander S.; Katz, Jacqueline M.; York, Ian A.
<x xml:space="preserve">Abstract</x> Background Vaccines against avian influenza viruses often require high hemagglutinin (HA) doses or adjuvants to achieve serological titers associated with protection against disease. In particular, viruses of the H7 subtype frequently do not induce strong antibody responses following immunization. Objectives To evaluate whether poor immunogenicity of H7 viruses is an intrinsic property of the H7 hemagglutinin. Methods We compared the immunogenicity, in naïve mice, of purified recombinant HA from two H7 viruses [A/Netherlands/219/2003(H7N7) and A/New York/107/2003(H7N2)] to that of HA from human pandemic [A/California/07/2009(H1N1pdm09)] and seasonal [A/Perth16/2009(H3N2)] viruses. Results After two intramuscular injections with purified hemagglutinin, mice produced antibodies to all HAs, but the response to the human virus HAs was greater than to H7 HAs. The difference was relatively minor when measured by ELISA, greater when measured by hemagglutination inhibition assays, and more marked still by microneutralization assays. H7 HAs induced little or no neutralizing antibody response in mice at either dose tested. Antibodies induced by H7 were of significantly lower avidity than for H3 or H1N1pdm09. Conclusions We conclude that H7 HAs may be intrinsically less immunogenic than HA from seasonal human influenza viruses.